A Hormonally Active Malignant Struma Ovarii - Carolina Lara; Dalia Cuenca; Latife Salame; Rafael Padilla-Longoria; Moisés Mercado (Case Reports in Oncological Medicine)
Struma ovarii is a rare monodermal variant of ovarian teratoma that contains at least 50% thyroid tissue. Less than 8% of struma ovarii cases present with clinical and biochemical evidence of thyrotoxicosis due to ectopic production of thyroid hormone and only 5% undergo malignant transformation into a papillary thyroid carcinoma. Only isolated cases of hormonally active papillary thyroid carcinoma developing within a struma ovarii have been reported in the literature. We report the case of a 36-year-old woman who presented with clinical signs and symptoms of hyperthyroidism as well as a left adnexal mass, which proved to be a thyroid hormone-producing, malignant struma ovarii.